Adult learning in the process of dealing with conflicts - Wajszczyk, Katarzyna (Adult Education Discourses, 2020)
The author presents conflict in structural and processual dimension as a possible situation of learning and characterizes a model in which conflicts can be dealt with. The model presented includes specific elements of working with conflict, which come into being in the interpersonal processes. The elements of conflict structure analyzed play crucial role in direct relations between the participants of conflict. Behaviors, reactions and the choice of the way of dealing with conflict is dependent on key structural categories such as: the object, the sides of conflict, resources needed, surrounding and conditions. These categories determine the realization of the process of dealing with a given conflict situation and impose direct reacting to changeable conditions. The reflection of the participants on themselves, their opponents and the whole conflict situation is an occasion for learning.